2020
DOI: 10.2147/ott.s274420
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Value of Ki67 in Patients with Stage 1–2 Endometrial Cancer: Validation of the Cut-off Value of Ki67 as a Predictive Factor</p>

Abstract: Objective The purpose of this study was to find a cut-off value of the immunohistochemical parameter Ki67 for stage I–II endometrial cancer. Materials and Methods The clinicopathological data of 318 patients with stages I–II endometrial cancer who received primary surgical treatment were retrospectively analyzed. A cut-off value of Ki67 for predicting recurrence of endometrial cancer was determined by using the receiver operating characteristic curve and the Youden inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 32 publications
3
28
2
Order By: Relevance
“…In another study evaluating 473 patients with stage I-III EC by Jia et al [31], a combined ratio obtained from percentages of estrogen, progesterone, Ki-67, and TP53 was reported to be a statistically significant factor for recurrence in multivariate analysis. Recently Jiang et al [32] reported that the Ki-67 index was an independent prognostic factor in stage I and II EC. Because the Ki-67 index was also a significant factor in an univariate analysis in lowrisk disease, they claimed that it could be helpful in the de- cision of performing an adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In another study evaluating 473 patients with stage I-III EC by Jia et al [31], a combined ratio obtained from percentages of estrogen, progesterone, Ki-67, and TP53 was reported to be a statistically significant factor for recurrence in multivariate analysis. Recently Jiang et al [32] reported that the Ki-67 index was an independent prognostic factor in stage I and II EC. Because the Ki-67 index was also a significant factor in an univariate analysis in lowrisk disease, they claimed that it could be helpful in the de- cision of performing an adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, immunohistochemical staining is still an economical, convenient, and time-saving method in clinical practice. ER, PR, Ki-67, and p53 are closely related to the prognosis of EC patients, Studies show that [19] the best cutoff value of Ki-67 in predicting endometrial cancer recurrence is 38%. Patients with positive ER and PR had a better prognosis, while those with p53 mutation and high Ki-67 had a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 12 For example, in breast cancer, the positive percentage of Ki67 immunohistochemistry ≥20% is defined as a high Ki67 state, which was used to evaluate the prognosis of the patient and guide the decision-making of adjuvant treatment options. 13 In endometrial cancer, Ki67 is also closely related to the prognosis of patients, especially in early stages of tumors, Ki67 is a powerful predictor that cannot be ignored, 14 but unfortunately, Ki67 still lacks an acceptable immunohistochemical positive threshold in EC. In summary, this study aimed to explore the prognostic factors associated with LNM in early-stage EC by including “apparent” early-stage EC patients, and to determine the optimal positive threshold of the immunohistochemical parameter Ki67 for predicting LNM in early-stage EC, to provide an auxiliary reference index for treatment and prognosis management of patients.…”
Section: Introductionmentioning
confidence: 99%